Perancangan Website UMKM “Boukara Flow” sebagai Media Informasi dan Promosi Menggunakan Aplikasi Blogger - Siti Husnul Afifah Thaher; Stevinda Mei Yulandari; Muhammad Rezha Arifin; Sularno; Novadilastri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This research aims to design a website for UMKM "Boukara Flow" as a medium for digital product information and promotion. The Boukara Flow business sells feather wire-based flower bouquets that can be customized according to consumer desires. The researcher's recommendation is to use the web for information and online purchases. With this web, it can make it easier for potential customers to get information about products. One of the webs that can be used is using the Blogger application which can be connected using a Google account. Using the blogger application makes it easier to get product information and can be used for product promotion.